1995
DOI: 10.1172/jci117872
|View full text |Cite
|
Sign up to set email alerts
|

MCF-7 breast cancer cells transfected with protein kinase C-alpha exhibit altered expression of other protein kinase C isoforms and display a more aggressive neoplastic phenotype.

Abstract: Increased protein kinase C (PKC) activity in malignant breast tissue and positive correlations between PKC activity and expression of a more aggressive phenotype in breast cancer cell lines suggest a role for this signal transduction pathway in the pathogenesis and/or progression of breast cancer. To examine the role of PKC in the progression of breast cancer, human MCF-7 breast cancer cells were transfected with PKC-a, and a group of heterogenous cells stably overexpressing PKC-a were isolated (MCF-7-PKCa). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
184
1
5

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(201 citation statements)
references
References 31 publications
11
184
1
5
Order By: Relevance
“…The a-isozyme of PKC, PKCa, is widely expressed in various tissues, and PKCa expression and activity have been found to be higher in some types of tumors than in normal tissues (Lahn et al, 2004;Michie and Nakagawa, 2005). Breast cancer cells engineered to express exogenous PKCa protein have been found to display a more aggressive phenotype (Ways et al, 1995). In addition to the role PKCa plays in cell transformation and tumorigenesis, studies have indicated that elevated PKCa activity in some human carcinoma cells, including breast cancer cells, is associated with an increased invasive or metastatic potential (Morse-Gaudio et al, 1998;Masur et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The a-isozyme of PKC, PKCa, is widely expressed in various tissues, and PKCa expression and activity have been found to be higher in some types of tumors than in normal tissues (Lahn et al, 2004;Michie and Nakagawa, 2005). Breast cancer cells engineered to express exogenous PKCa protein have been found to display a more aggressive phenotype (Ways et al, 1995). In addition to the role PKCa plays in cell transformation and tumorigenesis, studies have indicated that elevated PKCa activity in some human carcinoma cells, including breast cancer cells, is associated with an increased invasive or metastatic potential (Morse-Gaudio et al, 1998;Masur et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…PKC activity is involved in integrin-mediated responses including adhesion, motility and membrane ru ing (Lewis et al, 1996;Klemke et al, 1994;Yebra et al, 1995;Miyata et al, 1989). It can also a ect invasive behavior (Ways et al, 1995). PKC activation has been demonstrated as a controlling factor in the reabsorbtion activity exhibited by osteoclasts, a non-transformed cell type, responsible for bone remodeling (Moonga et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpressing PKCe in normal ®broblasts increased anchorage-dependent and -independent growth, whereas overexpressing PKCa and d inhibited growth (Cacace et al, 1993;Mischak et al, 1993;Watanabe et al, 1992;Yamaguchi et al, 1995). In contrast, overexpressing PKCa in MCF7 mammary tumor cells increased anchorage-dependent and independent growth (Ways et al, 1995). The fact that overexpressing an individual isozyme causes di erent growth responses depending on the cell type indicates that the relationship between individual PKCs and carcinogenesis is complicated and cannot be generalized.…”
Section: Introductionmentioning
confidence: 99%
“…While there is some evidence that increased PKC activity may be important in mammary carcinogenesis (Ways et al, 1995), there is little information on the role of individual PKCs in this process. To investigate the involvement of individual PKCs in mammary tumor (MT) promotion/progression, we compared PKC isozyme levels in MT cell lines that di er in growth rate and metastatic potential.…”
Section: Introductionmentioning
confidence: 99%